Russia Ukraine war and Turkey's diplomacy - DERMAN, GİRAY SAYNUR (My University, 2022)
The Russia-Ukraine War is an ongoing war involving Russia, Belarus and pro-Russian forces on the one hand and Ukraine on the other. It is a military activity that started in 2014 and grew in February 2022, after the President of Ukraine Viktor Yanukovych, who was dismissed after Euromaidan, asked Russia to send troops to the region due to the tension in Crimea. This war includes Russia's annexation of Crimea (2014), the Donbass War, cyber warfare, and political tensions. Claiming that Russia is protecting its geopolitical interests in the region, its citizens and deployed soldiers, President Vladimir Putin received parliamentary approval for the intervention. On February 21, 2022, Russia announced that it officially recognized the Donetsk and Luhansk People's Republics. On February 24, 2022, Russian leader Putin announced on television that they had started to invade Ukraine. After the diplomatic crisis in 2021, Russia, which made a military build-up in the regions close to the Ukrainian borders, started to invade Ukraine on a large scale on February 24, 2022. In this process, Turkey, as a regional actor, assumed a diplomatic mission between the two countries. Turkey is a prominent actor due to its commercial and politic. Turkey is a key actor due to its commercial and political relations with Russia and Ukraine, and its relations with the West as a NATO member. It is the only NATO member fighting for a lasting peace and ceasefire between the two countries. This article has been analyzed within the framework of Securitization Theory. In this article, Rusys Ukraine War and its effects, Turkey's diplomacy are discussed.al relations with Russia and Ukraine, and its relations with the West as a NATO member.

Rusya-Ukrayna Savaşı, bir yanda Rusya, Beyaz Rusya ve Rus yanlısı güçlerin, diğer yanda Ukrayna'nın dahil olduğu devam eden bir savaştır. 2014 yılında başlayan ve Euromaydan'ın ardından görevden alınan Ukrayna Devlet Başkanı Viktor Yanukoviç'in Kırım'daki gerginlik nedeniyle Rusya'dan bölgeye asker göndermesini istemesi üzerine Şubat 2022'de büyüyen bir askeri faaliyettir. Bu savaş, Rusya'nın Kırım'ı ilhakını (2014), Donbass Savaşı'nı, siber savaşı ve siyasi gerilimleri içermektedir. Rusya'nın bölgedeki jeopolitik çıkarlarını, vatandaşlarını ve konuşlu askerlerini koruduğunu iddia eden Devlet Başkanı Vladimir Putin, müdahale için meclisten onay aldı ve 21 Şubat 2022'de Rusya, Donetsk ve Luhansk Halk Cumhuriyetlerini resmen tanıdığını ilan etti. 24 Şubat 2022'de Rus lider Putin Ukrayna'yı işgal etmeye başladıklarını medyada duyurdu. 2021'deki diplomatik krizin ardından Ukrayna sınırlarına yakın bölgelerde askeri yığılma yapan Rusya, 24 Şubat 2022'de Ukrayna'yı büyük çapta işgal etmeye başladı. Bu süreçte Türkiye bölgesel aktör olarak iki ülke arasında diplomatik misyon üstlendi. Türkiye, ticari ve siyasi açıdan önemli bir aktördür. Türkiye, Rusya ve Ukrayna ile ticari ve siyasi ilişkileri ve bir NATO üyesi olarak Batı ile olan ilişkileri nedeniyle kilit bir aktördür. İki ülke arasında kalıcı bir barış ve ateşkes için savaşan tek NATO üyesidir. Bu makale güvenlikleştirme teorisi çerçevesinde analiz edilmiştir. Bu makalede Rusya Ukrayna Savaşı ve etkileri, Türkiye'nin diplomasisi, Rusya ve Ukrayna ile ilişkileri ve NATO üyesi olarak Batı ile ilişkileri tartışılmaktadır
Keywords: Rusya Federasyonu; Ukrayna; Türkiye; Savaş; Diplomasi; Russian Federation; Ukraine; Turkey; War; Diplomacy.